2013
DOI: 10.1016/j.cell.2013.01.012
|View full text |Cite
|
Sign up to set email alerts
|

DNA Synthesis Is Required for Reprogramming Mediated by Stem Cell Fusion

Abstract: SummaryEmbryonic stem cells (ESCs) can instruct the conversion of differentiated cells toward pluripotency following cell-to-cell fusion by a mechanism that is rapid but poorly understood. Here, we used centrifugal elutriation to enrich for mouse ESCs at sequential stages of the cell cycle and showed that ESCs in S/G2 phases have an enhanced capacity to dominantly reprogram lymphocytes and fibroblasts in heterokaryon and hybrid assays. Reprogramming success was associated with an ability to induce precocious n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 73 publications
(106 reference statements)
6
65
1
Order By: Relevance
“…Whether the drop in histone PTM levels after DNA replication affects gene expression and could provide an opportunity to modify the transcription program remains an open question (Steffen and Ringrose 2014). We envision that it could provide a window of opportunity to rewire cell fate (Fisher and Mechali 2003;Tsubouchi et al 2013). By following histones from the moment of their incorporation, we found that most PTMs are not imposed on new histones in a rapid replication-coupled manner.…”
Section: Cell Cycle Withdrawal Impacts Histone Ptm Levelsmentioning
confidence: 82%
See 1 more Smart Citation
“…Whether the drop in histone PTM levels after DNA replication affects gene expression and could provide an opportunity to modify the transcription program remains an open question (Steffen and Ringrose 2014). We envision that it could provide a window of opportunity to rewire cell fate (Fisher and Mechali 2003;Tsubouchi et al 2013). By following histones from the moment of their incorporation, we found that most PTMs are not imposed on new histones in a rapid replication-coupled manner.…”
Section: Cell Cycle Withdrawal Impacts Histone Ptm Levelsmentioning
confidence: 82%
“…We further envision that this mode of PTM maintenance could explain how cell cycle speed and withdrawal impact on cellular plasticity. DNA replication could be instrumental to reset epigenetic states (Tsubouchi et al 2013), and, by revealing how histone PTMs are maintained across the cell cycle, our findings pave the way to understanding how cellular identity and reprogramming potential are connected with cell proliferation (Guo et al 2014). …”
Section: Cell Cycle Withdrawal Impacts Histone Ptm Levelsmentioning
confidence: 99%
“…18 It is interesting to note that replication of DNA also appears to aid certain cell fusion experiments. 19 DNA synthesis may contribute to reprogramming in a similar manner to mitotic transition in so much as transcriptional regulators may be displaced by the DNA replication machinery and histone decorations may be changed at the time of histone incorporation into replicated DNA. 20 In the same vein, other aspects of the cell cycle that are associated with changes in cellular identity exist 21 and are likely to impact reprogramming by facilitating gene expression change.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…Foshay et al showed that only pluripotent stem cells can induce pluripotency in somatic cells [16]. Factors, which influence reprogramming by cell fusion, include polycomb group proteins [17], activation-induced cytidine deaminase (AID)-dependent demethylation [18], and DNA synthesis [16,19]. However, the differentiation capacity of hybrid cells compared with the parental pluripotent stem cells is less studied, especially in human hybrids.…”
mentioning
confidence: 99%
“…Cell fusion was used as an approach to study reprogramming of somatic cells toward pluripotency [3,[9][10][11][12][13][14][15][16][17][18][19][20]. Shortly after fusion, hybrid cells acquire similar characteristics as the parental pluripotent stem cells.…”
mentioning
confidence: 99%